METHODS FOR OVERCOMING COMMUNICATION DIFFICULTIES - Laguta, Tatiana; Verzhanskaya, Olga (New Collegium, 2020)
The work is dedicated to the study of the phenomenon of "communicative failure." The presence of identical concepts, complexity and diversity of this phenomenon, the variability of its causes, cause at the same time the interest of scientists and division of views on this phenomenon. The relevance of the study is to explore the means to optimize communication in a cross-cultural interaction.